Hepatic perfusion changes in patients with liver metastases: comparison with those patients with cirrhosis. Issue 4 (April 1993) - Leen, E; Goldberg, J A; Anderson, J R; Robertson, J; Moule, B; Cooke, T G; McArdle, C S
Abstract : Previous studies using dynamic scintigraphy have shown that the measurement of changes in hepatic perfusion may be exploited to detect liver metastases. Similar hepatic haemodynamic changes also occur in cirrhosis, however, thereby reducing the diagnostic power of the technique. The ability of duplex colour Doppler sonography (DCDS) to differentiate between the changes in liver perfusion in patients with cirrhosis and those with hepatic metastases was assessed. Hepatic arterial and portal venous blood flows were measured in 30 control subjects, 20 patients with cirrhosis, and 55 patients with overt liver metastases. The Doppler perfusion index (DPI) (the rate of hepatic arterial to total liver blood flow) and the congestive index (ratio of the cross sectional area of the vessel to time averaged velocity of blood flow in the vessel) of the hepatic artery (HCI) and portal vein (PCI) were calculated. The hepatic arterial blood flow of the cirrhotic and metastatic groups was significantly raised compared with that of controls, and the portal venous blood flow of the former groups were reduced (p < 0.0001). The DPIs of the cirrhotic and metastatic groups were therefore significantly raised compared with those of controls (p < 0.0001). No significant difference was noted in HCI values between the three groups. The PCI values of the cirrhotic group, however, were significantly raised compared with those of controls and patients with metastases (p < 0.0001). The data suggest that DCDS measurement of PCI may be of value in differentiating between the hepatic perfusion changes caused by cirrhosis and those resulting from hepatic metastases, thereby increasing the diagnostic power of this technique.